Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.3 - Fractional Exponents - Problem Set 11.3 - Page 489: 78



Work Step by Step

First, we will simplify the expression within the parenthesis using the rule $\frac{a^{m}}{a^{n}}=a^{m-n}$: $(\frac{2a^{\frac{1}{2}}}{3a^{\frac{1}{4}}})^{3}$ =$(\frac{2}{3}\times\frac{a^{\frac{1}{2}}}{a^{\frac{1}{4}}})^{3}$ =$(\frac{2}{3}\times a^{\frac{1}{2}-\frac{1}{4}})^{3}$ =$(\frac{2}{3}\times a^{\frac{2-1}{4}})^{3}$ =$(\frac{2}{3}\times a^{\frac{1}{4}})^{3}$ Now, we raise each term in the expression to the power of $3$: $(\frac{2}{3}\times a^{\frac{1}{4}})^{3}$ =$(\frac{2}{3})^{3}\times (a^{\frac{1}{4}})^{3}$ =$(\frac{2^{3}}{3^{3}})\times (a^{\frac{3}{4}})$ =$(\frac{8}{27})\times (a^{\frac{3}{4}})$ =$\frac{8a^{\frac{3}{4}}}{27}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.